2018
DOI: 10.1111/jcmm.13630
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in the pathogenesis of systemic scleroderma: An overview

Abstract: Systemic sclerosis (SSc) is a rare disorder of the connective tissue characterized by fibrosis of the skin, skeletal muscles and visceral organs. Additional manifestations include activation of the immune system and vascular injury. SSc causes disability and death as the result of end‐stage organ failure. Two clinical subsets of the SSc are accepted: limited cutaneous SSc (lc‐SSc) and diffuse cutaneous SSc (dc‐SSc). At present, the aetiology and pathogenesis of SSc remain obscure, and consequently, disease out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 58 publications
(143 reference statements)
1
43
0
2
Order By: Relevance
“…We find that SSc patients exhibit increased oxidative stress and AP sites, which is in line with previous studies showing that oxidative stress is implicated in the development and perpetuation of SSc ( 7 , 40 ). Indeed, several oxidative stress biomarkers, such as malondialdehyde (a marker of lipid peroxidation), nitric oxide, and endogenous nitric oxide inhibitor asymmetric dimethylarginine are increased in the blood of SSc patients ( 41 ). In contrast, antioxidative biomarkers, such as superoxide dismutase and vitamin C, are lower in SSc patients’ blood ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…We find that SSc patients exhibit increased oxidative stress and AP sites, which is in line with previous studies showing that oxidative stress is implicated in the development and perpetuation of SSc ( 7 , 40 ). Indeed, several oxidative stress biomarkers, such as malondialdehyde (a marker of lipid peroxidation), nitric oxide, and endogenous nitric oxide inhibitor asymmetric dimethylarginine are increased in the blood of SSc patients ( 41 ). In contrast, antioxidative biomarkers, such as superoxide dismutase and vitamin C, are lower in SSc patients’ blood ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oxidative stress is involved in the pathogenesis of SSc [87]. That is, SSc patients are characterized by increased production of ROS in the skin, visceral fibroblasts, and endothelial cells, as well as by reduced concentrations of various antioxidants, including antioxidant vitamins (ascorbic acid, α-tocopherol, β-carotene) and minerals (zinc, selenium) [88]. Also, oxidative stress has been observed in patients with RA.…”
Section: Oxidative Stress Causes Dna Damage That Activates the Immunementioning
confidence: 99%
“…So far, there are no data regarding the role of CTSS in the development of SSc-ILD, but previous studies revealed the contribution of ROS to this complication. For instance, there are several reports demonstrating the increased concentration of ROS in SSc patients, [26][27][28][29] especially in patients with SSc-ILD. 30,31 In addition, a perturbation of mitochondria homeostasis in alveolar macrophages has been reported in idiopathic pulmonary fibrosis (IPF) that shares a part of the pathological process with SSc-ILD, especially its fibrotic phase.…”
Section: Discussionmentioning
confidence: 99%